VALUE (X 2) + FINE = DAMAGES? NOTES ON THE IMPOSITION OF SANCTIONS BY THE COURTS OF CHIEFS (SENIOR TRADITIONAL LEADERS) AND HEADMEN - Elmarie Knoetze (Obiter, 2014)
The main fora for the adjudication of customary-law cases on a daily basis are the courts of chiefs (senior traditional leaders) and headmen (the so-called traditional courts) which were given recognition by the Black Administration Act. Section 12 of the Act conferred civil jurisdiction on designated chiefs (or senior traditional leaders) and headmen to hear cases arising out of Black law and custom, whereas criminal jurisdiction was regulated by section 20 of the same. It is the purpose of this note to consider the jurisdiction of these courts in so far as it relates to their judgments, or, in other words, the imposition of sanctions or orders. This will be followed by a consideration of the orders or sanctions that may be given by traditional courts in terms of section 10 of the Traditional Courts Bill. The note will be concluded by a discussion of the nature of customary sanctions, taking into account the current (official) law, proposed law (in terms of the Traditional Courts Bill) as well as the living law. For purposes of the discussion, the imposition of sanctions by courts with civil jurisdiction will be emphasized and used as examples. To reflect the living law, regard will be had to a number of case studies compiled by Prof FA de Villiers, former professor of law at the University of the Western Cape (information obtained from and used with permission of the researcher). The case studies were recorded from official reports of chiefs‟ court judgments from 1995-2004 of the BaNkuna traditional authority to the Magistrates‟ Court with concurrent jurisdiction, Limpopo Province.